Twelve unidentified skeletons as remains of an epidemic or famine in Northern Finland - Sisko Huumonen; Terttu Särkioja; Sinikka Salo; Markku Niskanen; Heli Maijanen4; Jorma Hirvonen (My University, 2022)
Skeletal remains of 12 individuals were found in a grave in a tar-burning pit. There were no coffins or other belongings to help with identification or reveal the cause of death. Methods: Forensic osteological and odontological methods were used to establish sex, age and height. Histological and chemical tests, including the determination of C-14 content, were applied to dating the skeletal remains. Results: Out of 12 skeletons, 8 were adults; 5 females, 2 males and 1 probable female. Four skeletons belonged to children (ages 1-12 years). The bones had been in the grave for more than 100 years as concluded from the deterioration of the distal parts, embrittling of the surface to 1 mm depth. C-14 results gave the radiocarbon years 95 +/- 65 Bp (before present, i.e., 1950). The calibrated years correspond to two time periods, 1670–1780 AD and 1798–1944 AD, as a possible period of death. Conclusions: Starvation and illnesses are the most plausible explanations for the deaths. Historical studies show that during the 17th and 19th centuries, there were famines in Finland accompanied by severe infections (severe famines in the years 1866–1868 and 1696– 1697), forcing a lot of people to leave their homes.